Christmas in camelot eaudiobook - Osborne, Mary Pope (Magic Tree House: Merlin Missions, 2006)
When Jack and Annie receive an invitation to spend Christmas Eve in Camelot—a magical place that exists only in myth and fantasy—they know they are in for their biggest adventure yet. What they don't know is that the invitation will send them on a quest to save Camelot. Can they succeed even though Camelot's greatest knights have failed? Did you know that there’s a Magic Tree House book for every kid? Magic Tree House: Adventures with Jack and Annie, perfect for readers who are just beginning chapter books Merlin Missions: More challenging adventures for the experienced reader Super Edition: A longer and more dangerous adventure Fact Trackers: Nonfiction companions to your favorite Magic Tree House adventures Have more fun with Jack and Annie at MagicTreeHouse.com!